Industrial community energy systems: Simulating the role of financial incentives and societal attributes - Eslamizadeh, Sina; Ghorbani, Amineh; Costa, Rafael Castelo Branco Ferreira; Künneke, Rolf; Weijnen, Margot (Frontiers in Environmental Science, 2022)
Considering that the industrial sector consumes almost one-third of the energy demand globally, it is an urgent call to reduce the carbon footprints in this sector. Among different approaches to meet this goal, such as the employment of carbon capture technologies and increasing energy efficiency within industries, transitioning to renewable electricity (RE) would be another outlook to reduce the carbon footprints and increase the energy security of the industries. Collective power generation within communities has shown to be feasible and promising in the industrial sector, where groups of industries collaborate to generate energy and meet their energy demand. In this research, we investigated how the initiation and continuation of industrial community energy systems (InCES) among companies can take place and which financial incentives the government can introduce to support these initiatives. We built an agent-based model that incorporates cost-benefit analysis and cultural factors in the decision making process of industries, to assess the feasibility of initiating/joining an InCES by industries. This study shows that the FIT mechanism had the worst performance in incentivizing the establishment of an InCES among industries. In contrast, the TAX incentive showed the best performance in mobilizing the investments towards InCES. Similarly, the TAX incentive showed relatively superior performance in electricity generation, the number of established InCESs, and the number of companies joining each InCES. Despite the better performance of the TAX incentive, it was also the most expensive option for the governments as a significant share of the establishment costs of an InCES was put on the shoulders of the governments.